Analisis Kualitas Aplikasi Perpustakaan sebagai Layanan Publik Digital: Perspektif Mahasiswa Universitas Tidar - Raafi Grio; Aldora Atha Faisa; Imeldha Zazckia Poetri; Nurul Afifah Hafizh; Damai Larasati; Joko Tri Nugraha (Jurnal Pustaka Ilmiah, 2026)
This study aims to describe Tidar University students’ assessment of the service quality of a digital library application as part of technology-based public services. A quantitative descriptive approach was employed to analyze the perceptions of 96 respondents using the five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. Data were collected through an online questionnaire and analyzed using Microsoft Excel and SPSS. The results indicate that most students gave positive assessments of the application, particularly in terms of interface design, clarity of collection information, ease of navigation, and data security. However, several issues were identified, including inconsistent information updates, access disruptions, and uneven technical support. Overall, the application is considered sufficiently effective in supporting students’ academic needs, although improvements are still required in system stability, response speed, and feature development to better accommodate users’ needs across different study programs. These findings are expected to provide an empirical basis for library managers in designing more adaptive and sustainable digital service improvements.